Tandem autologous hematopoietic stem cell transplantation for patients with multiple myeloma: a systematic review and meta-analysis - Hongtao Li; Yaxin Zheng; Kehai Gao; Chen Tian (Hematology)
To evaluate whether patients with multiple myeloma (MM) could benefit from tandem autologous hematopoietic stem cell transplantation (auto-HSCT), PubMed, Embase, Web of Science and Cochrane Library databases were systematically searched, and 10 eligible studies were included after data extraction and quality evaluation. Meta-analysis showed that compared to single autologous hematopoietic stem cell transplantation, tandem auto-HSCT does not improve OS, EFS or efficacy in MM patients, and may even lead to higher treatment-related mortality (TRM). MM patients who received autologous tandem allogeneic HSCT did not achieve better response compared to tandem autologous HSCT. In summary, compared to single autologous hematopoietic stem cell transplantation, tandem autologous hematopoietic stem cell transplantation cannot provide survival advantages for MM patients, and MM patients cannot benefit from autologous tandem allogeneic hematopoietic stem cell transplantation.